Molecular and Proteomic Analysis of Levofloxacin and Metronidazole Resistant Helicobacter pylori - Hanafi, Aimi; Lee, Woon Ching; Loke, Mun Fai; Teh, Xinsheng; Shaari, Ain; Dinarvand, Mojdeh; Lehours, Philippe; Mégraud, Francis; Leow, Alex Hwong Ruey; Vadivelu, Jamuna; Goh, Khean Lee (Frontiers in Microbiology, 2016)
Antibiotic resistance in bacteria incur fitness cost, but compensatory mechanisms may ameliorate the cost and sustain the resistance even under antibiotics-free conditions. The aim of this study was to determine compensatory mechanisms of antibiotic resistance in H. pylori. Five strains of levofloxacin-sensitive H. pylori were induced in vitro to develop resistance. In addition, four pairs of metronidazole-sensitive and -resistant H. pylori strains were isolated from patients carrying dual H. pylori populations that consist of both sensitive and resistant phenotypes. Growth rate, virulence and biofilm formating ability of the sensitive and resistant strains were compared to determine effects of compensatory response. Proteome profiles of paired sensitive and resistant strains were analyzed by liquid chromatography / mass spectrophotometry (LC/MS). Although there were no significant differences in growth rate between sensitive and resistant pairs, bacterial virulence (in terms of abilities to induce apoptosis and form biofilm) differs from pair to pair. These findings demonstrates the complex and strain-specific phenotypic changes in compensation for antibiotics resistance. Compensation for in vitro induced levofloxacin resistance involving mutations of gyrA and gyrB was functionally random. Furthermore, higher protein translation and non-functional protein degradation capabilities in naturally-occuring dual population metronidazole sensitive-resistant strains may be a possible alternative mechanism underlying resistance to metronidazole without mutations in rdxA and frxA. This may explain the lack of mutations in target genes in approximately 10% of metronidazole resistant strains.